Nyai's Representation in Bumi Manusia Film (Analysis of Semiotics of Bumi Manusia Films) - Shinta Dwi Andriani Budiartho; Poppy Febriana (Universitas Muhammadiyah Sidoarjo, 2021)
Nyai's Reception at Bumi Manusia (Semiotic Analysis of Cristian Metz Film) This thesis has not been published. Faculty of Business, Law and Social Sciences. Muhammadiyah University of Sidoarjo. This study aims to find out the content of the written film contains many sets of signs and needs to be understood so that a message conveyed by the film director is right on target. The film Bumi Manusia is the object of this research, there is a Nyai character who lifts the success of this film. Nyai has a certain connotation and stigma, which in the Big Indonesian Dictionary is translated as a call intended for women who are not or are already married. Nyai is the same as concubine. That's what makes researchers intrigued to examine the role of Nyai Ontosoroh in the film Bumi Manusia entitled